From Coagulation to Disinfection: Key Steps and Challenges in Wastewater Treatment - Wang Shengyuan (E3S Web of Conferences)
Wastewater treatment is a critical process to ensure the safe management of water for domestic, industrial and municipal use. The importance of wastewater treatment has become more pronounced as water consumption increases and environmental regulations become more stringent. Wastewater treatment plants remove harmful contaminants from wastewater and produce clean discharges that meet regulatory standards through a series of mechanical, biological, and chemical processes such as coagulation, sedimentation, filtration, and disinfection. This paper explores the advantages and disadvantages of each wastewater treatment stage and evaluates the wastewater treatment infrastructure in the United States and China. The U.S. has better wastewater treatment systems, while China still has inadequate wastewater treatment facilities in rural areas. Wastewater reuse is an important part of achieving a sustainable future, and further development and implementation of these systems can help improve global water management.